PLACE OF ANGIOTENSIN II RECEPTOR ANTAGONISTS IN ARTERIAL HYPERTENSION THERAPY - S. A. Boytsov; I. P. Kolos (Рациональная фармакотерапия в кардиологии)
Angiotensin II receptor antagonists (ARA) established their position recently duet to new indications above arterial hypertension (HT). These are chronic heart failure, history of myocardial infarction, atrial fibrillation and metabolic syndrome. Analysis of evidence basis, including recently published biggest international clinical studies, was performed in the article. Data demonstrate that ARA can be effectively and safely used in wide clinical practice for improvement of life quality and life prolongation in patients with HT.